2004
DOI: 10.1097/00001756-200405190-00005
|View full text |Cite
|
Sign up to set email alerts
|

Affective picture perception: gender differences in visual cortex?

Abstract: Activity in extrastriate visual cortex is greater when people view emotional relative to neutral pictures. Prior brain imaging and psychophysiological work has further suggested a bias for men to react more strongly to pleasant pictures, and for women to react more strongly to unpleasant pictures. Here we investigated visual cortical activity using fMRI in 28 men and women during picture viewing. Men and women showed reliably greater visual cortical reactivity during both pleasant and unpleasant pictures, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
126
4
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(150 citation statements)
references
References 21 publications
16
126
4
4
Order By: Relevance
“…Females had stronger activation in the occipital cortex (BA17/19), and males had more extensive activation in frontal cortex, the inferior temporal gyrus (BA 37), the middle temporal gyrus (BA21), the posterior cingulate, and the amygdala. A similar pattern of gender difference for activation in emotional picture perception has been reported by others (Wrase et al, 2003;Sabatinelli et al, 2004). Comparison of the age dependent responses in our own data for the emotional pictures task shows relatively high absolute activity in the amygdala, left parahippocampal gyrus and ventral occipital cortex (BA 18,19) in the youngest group, and left inferior frontal and left temporal gyri (BA 47) in the oldest group.…”
Section: Age and Gender Specific Activationsupporting
confidence: 89%
“…Females had stronger activation in the occipital cortex (BA17/19), and males had more extensive activation in frontal cortex, the inferior temporal gyrus (BA 37), the middle temporal gyrus (BA21), the posterior cingulate, and the amygdala. A similar pattern of gender difference for activation in emotional picture perception has been reported by others (Wrase et al, 2003;Sabatinelli et al, 2004). Comparison of the age dependent responses in our own data for the emotional pictures task shows relatively high absolute activity in the amygdala, left parahippocampal gyrus and ventral occipital cortex (BA 18,19) in the youngest group, and left inferior frontal and left temporal gyri (BA 47) in the oldest group.…”
Section: Age and Gender Specific Activationsupporting
confidence: 89%
“…A recent neuroimaging study (Sabatinelli et al, 2004) showed that erotic pictures elicited a greater activity in extrastriate visual cortex in men compared with women, suggesting a male visual bias for erotic stimuli. Our findings, however, indicate a strong selectivity of ERP responses to erotic contents in women, suggesting that "erotic bias" can exist in both genders, although the extent to which it is expressed may depend on research methods, in particular their temporal and spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of previous research on gender differences in affective processing (Bellezza, Greenwald, & Banaji, 1986;Bradley, Codispoti, Sabatinelli, & Lang, 2001;Sabatinelli, Flaisch, Bradley, Fitzsimmons, & Lang, 2004;Wrase et al, 2003), and involving the IAPS in particular (Lang et al, 2008), we expected that participant gender might modulate the valence and arousal ratings. Therefore, we calculated .96], t(898) = 92.62, p < .001.…”
Section: Gender Differencesmentioning
confidence: 99%